Sex-sorting of Spermatozoa in Mammals: A Review - Jain, Asit; Jain, Tripti; Yathish H. M; B. Prakash; Sharma , Ashwani (Journal of Livestock Biodiversity, 2025)
Sex-preselection by separating the male- and female-bearing spermatozoa is vital for efficient reproduction. In the past, various techniques have been evolved for sexing of semen. They were based on differences in the weight, density, size, motility, surface charges and surface antigen structures etc. There are many reports which have documented the favorable results but they have paucity of scientific validation. A flow cytometric sperm sorting is the best method for separation of X- and Y-chromosome bearing sperm, which is commonly used and relies on the difference of their DNA content. Efforts are in place to exploit this technique in animals. To date, the flow cytometrically sorted sperm are used in the production of sex preselected offspring by surgical intratubal insemination, in vitro fertilization and embryo transfer and intracytoplasmic sperm injection (ICSI). In last decade, the high-speed sperm sorting with the orienting nozzle resulted in production of X and Y-sperm with 90% accuracy at the rate of 2-6 million sperm per hour. This application can enable to accomplish more conventional technology for both artificial insemination and cryopreservation of X or Y sperm in farm animals. The process of commercialization of sexed sperm has accelerated recently. However, this technology has some impediments with respect to cost, implementation and pregnancy rate in comparison with insemination with fresh semen. Despite these limitations, production of sexed semen usually followed by cryopreservation is being used commercially for cattle and horse production in different parts of the world.